2017
DOI: 10.4236/jep.2017.82010
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the Use of Waste as Raw Materials for Biogas Production

Abstract: Anthropic methane emissions can largely be prevented or minimized using technologies that are already available. One such technology is anaerobic digestion (AD), which is used commercially around the world, especially in Europe and the United States, where some challenging targets have been set to diversify the energy mix with more renewable energy. This foresight study was designed to identify which technological solutions out of the many options available for biogas production are attracting most interest, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…They also outlined biological methods like composting, micro aeration, and container closure to optimize biogas production. Grando et al (2017) surveyed raw materials commonly used for biogas production, such as sludge, biological waste, wastewater, livestock waste, and agricultural waste. Awe et al, (2017) demonstrated that is an effective renewable energy sources for fuel and chemicals production, including hydrogen and synthetic gas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They also outlined biological methods like composting, micro aeration, and container closure to optimize biogas production. Grando et al (2017) surveyed raw materials commonly used for biogas production, such as sludge, biological waste, wastewater, livestock waste, and agricultural waste. Awe et al, (2017) demonstrated that is an effective renewable energy sources for fuel and chemicals production, including hydrogen and synthetic gas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Different wastes were used as a raw material for the biogas production such as algae with aquatic plants, industrial waste, municipal solid waste, food waste, cellulosic waste, agricultural waste, livestock waste, and sewage sludge. Among the above, sewage sludge has a predominant source [19]. Mixture of different raw materials was also used for the biogas production such as cow dung, pig manure, cow urine, and fecal matter [7].…”
Section: Characterization Of Iron Oxidementioning
confidence: 99%
“…biogas consists of methane (50-75%), carbon dioxide (25-50 %), as well as small amounts of other gases such as nitrogen (0-10%), hydrogen (0-1%), hydrogen sulfide (0-3%), and oxygen (0-2%) [10]. the biofuel is renewable and environmentally clean which significantly decreases the fossil fuel consumption [11]. Anaerobic digestion is a useful energy production technique.…”
Section: Introductionmentioning
confidence: 99%